Control interno como herramienta para la detección de fraudes y errores en la cooperativa de ahorro y crédito "Mushuc Runa" LTDA - Chicaiza Molina, Mercy Fernanda (2019)
The present project was carried out in the Savings and Credit MUSHUC RUNA Limited Cooperative which is one of the financial institutions of the indigenous sector that focuses on granting credits to merchants and micro entrepreneurs at a national level. Within this framework it is important to point out that as in any entity, whether large or small, there are problems, such as that the personnel working in the entity is not familiar with the manuals and policies that are applied in the Cooperative, so they are ready to make mistakes or justify that to commit fraud. For this reason, this research project aims to analyze the level of compliance of the internal control system in the Savings and Credit Mushuc Runa Limited Cooperative and its impact on financial stability. The research methodology applied during this process was a bibliographic-documentary, exploratory, descriptive, and explanatory and field type, which helped to determine the problems that exist in the place and to continue with the development of this project. The results obtained from this analysis was to identify that the employees who work in this entity are not familiar with the SCI because the personnel in charge of socializing do not perform it correctly, also through the evaluation of the internal control system it was possible to determine that this entity has some software that helps detect fraud and errors, preventing unauthorized people from accessing computer equipment and using the entity's data in an improper manner. It should be noted that the entity benefited from the familiarization of the internal control system to all personnel working in the institution, with this performance was improved in the different activities and even better relations were established between the different areas of the cooperative motivating the propitious development in its functions. It is worth noting that this research project was of great help for the Mushuc Runa Cooperative since it receives all information resulting from research conducted by university students whose purpose is to establish solutions, suggestions or ideas that allow managers to make decisions on improvement of the entity allowing the cooperative to be competitive within the financial market and to achieve the permanence, solvency and reliability of its clients.